1991
DOI: 10.1080/00288330.1991.9516468
|View full text |Cite
|
Sign up to set email alerts
|

Thermal avoidance in inanga,Galaxias maculatus(Jenyns), from the Waikato River, New Zealand

Abstract: Temperature avoidance behaviour of inanga, Galaxias maculatus, was studied in the laboratory using a two-choice tank. The final preferred temperature of inanga is about 20°C but fish acclimatised to cooler temperatures (15 and 17°Q prefer warmer waters (up to 23 and 26°C, respectively). Fish acclimatised to temperatures of 15,17, and 20°C showed total avoidance at 29.5,31, and 31.5°C, respectively. Water temperature therefore is an important factor influencing upstream migration and distribution of inanga and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Lake Purrumbete is fresh, Lake Bullen Merri is saline and Lake Corangamite hypersaline. Laboratory‐based studies provide little evidence to suggest that oxygen (Boubee et al , 1991), temperature (Dean & Richardson, 1999) or turbidity (Rowe et al , 2002) reach sufficiently extreme levels to negatively affect the galaxid populations, but salinity in Lake Corangamite can exceed the laboratory determined tolerance levels of G. maculatus (LD 50 62) (Chessman & Williams, 1975). Notably, the LD 50 identified in Chessman & Williams (1975) is well below the salinities in which this species was regularly found in Lake Corangamite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lake Purrumbete is fresh, Lake Bullen Merri is saline and Lake Corangamite hypersaline. Laboratory‐based studies provide little evidence to suggest that oxygen (Boubee et al , 1991), temperature (Dean & Richardson, 1999) or turbidity (Rowe et al , 2002) reach sufficiently extreme levels to negatively affect the galaxid populations, but salinity in Lake Corangamite can exceed the laboratory determined tolerance levels of G. maculatus (LD 50 62) (Chessman & Williams, 1975). Notably, the LD 50 identified in Chessman & Williams (1975) is well below the salinities in which this species was regularly found in Lake Corangamite.…”
Section: Discussionmentioning
confidence: 99%
“…It has a remarkably flexible life history, capable of completing its life cycle within lakes and rivers (Pollard, 1971 a , b , 1972 a , b ) or equally utilizing marginal catadromy (McDowall, 1968 a , 2010). The adaptability of life style is reflected in its tolerance of a wide variety of environmental conditions including salinities ranging between 1 and 62 (Chessman & Williams, 1975), temperatures between 11 and 29° C (Boubee et al , 1991; Chapman et al , 2006) and dissolved oxygen levels of 1 mg l −1 for relatively short periods of time (Dean & Richardson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The method facilitates the determination of the effects of gradual temperature changes and allows ontogenetic shifts in temperature preferences to be calculated. Boubee et al (1991) showed experimentally that the final preferred temperature of Galaxias maculates resident in New Zealand is about 20 o C and temperatures above 29.5 o C were totally avoided.…”
Section: Behavioural Preferences and Avoidancementioning
confidence: 99%
“…Gerald and Spezzano, 2005). Thermal gradient tanks have been used to determine temperature preferences (Cherry and Cairns, 1982;Boubee et al, 1991;Richardson et al, 1994). This technique involves the establishment of a temperature gradient that is then used to evaluate the temperatures preferred or avoided by various organisms.…”
Section: Behavioural Preferences and Avoidancementioning
confidence: 99%
“…It is unclear from the available data whether there are different responses to temperature shown by the minnows from the two areas, however one might suspect a priori that gravid females or juveniles may be particularly susceptible to thermal stress. Thermal avoidance may also reflect scope for exercising choice: Galaxias maculatus avoids a plume of warm water discharged from a power station (Boubee et al 1991). The predation rate on flying ants and adult Diptera, i.e.…”
Section: ±5 150 ± 149mentioning
confidence: 99%